FISCAL AND MONETARY POLICY INTERACTION IN INDONESIA : A VAR ANALYSIS FROM 2000-2013 - Eko Sumando (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2015)
The paper examines the interaction of fiscal and monetary policy and the effectiveness of inflation Targeting Framework (ITF) using vector Autoregression (VAR) method in indonesia from 2000 to 2013. The study uses model that is estimated from the Nordhaus approach and the secondary data obtained from federal Reserve St, Lois (FRED) and CEIC. The study shows the absence of fiscal dominance in Indonesia and the ITF is moderately effective in achieving targeted inflation rate. Tightening monetary policy by Bank Indonesia is able to effect almost 30 per cent the change inflation variability after two year . Expansionary fiscal policy is only able to reduce the unemployment in a very short term. Which will potentially lead to inflation. The result suggest that in a short term the coordination of fiscal and monetary policy is needed and effective to achieve loer unemployment and minimize the gap between the targeted and actual inflation.